Digital logic testing and simulation - Miczo, Alexander (John Wiley & Sons, 2003)
The book reviews the building blocks of a successful testing strategy and guides the reader on choosing the best solution for a particular application. Digital Logic Testing and Simulation, Second Edition covers such key topics as: - Binary Decision Diagrams (BDDs) and cycle-based simulation - Tester architectures/Standard Test Interface Language (STIL) - Practical algorithms written in a Hardware Design Language (HDL) - Fault tolerance - Behavioral Automatic Test Pattern Generation (ATPG) -The development of the Test Design Expert (TDX), the many obstacles encountered and lessons learned in creating this novel testing approach Up-to-date and comprehensive, Digital Logic Testing and Simulation is an important resource for anyone charged with pinpointing faulty products and assuring quality, safety, and profitability.